The rise in student loan defaults - Mueller, Holger M.; Yannelis, Constantine (Journal of Financial Economics, 2019)
We examine the rise in student loan defaults in the Great Recession by linking administrative student loan data at the individual borrower level to student loan borrowers’ individual tax records. A Blinder-Oaxaca style decomposition shows that shifts in the composition of student loan borrowers and the massive collapse in home prices during the Great Recession can each account for approximately 30% of the rise in student loan defaults. Falling home prices affect student loan defaults by impairing individuals’ labor earnings, especially for low income jobs. By contrast, when comparing the default sensitivities of homeowners and renters, we find no evidence that falling home prices affect student loan defaults through a home equity-based liquidity channel. The Income Based Repayment (IBR) program introduced by the federal government in the wake of the Great Recession reduced both student loan defaults and their sensitivity to home price fluctuations, thus providing student loan borrowers with valuable insurance against negative shocks.